Development of a tool for the structural design of the vertical load‐bearing capacity of unreinforced masonry: Entwicklung eines Tools zur Bemessung der Vertikaltragfähigkeit von unbewehrtem Mauerwerk. Issue 4 (21st August 2017) - Suda, Raphael; Schranz, Christian; Jäger, Andreas
Abstract: Before the introduction of EC 6, simple codes permitted masonry to be designed manually. The simplified procedure according to EN 1996‐3 still allows manual design, but its application is restricted. Therefore, a more laborious design according to EN 1996‐1‐1 is often required. This article presents a newly developed software tool, which facilitates the structural design of the vertical load‐bearing capacity of unreinforced masonry according to EN 1996‐1‐1. The tool is intuitive to use and has been developed based on experience from working in the field. The tool assists the planner in making decisions during the masonry design process. This article describes and explains the implemented, theoretical assumptions as well as the software tool NRd ‐Pro‐Tool itself. This software tool facilitates simple, clear und transparent structural design of the vertical load bearing capacity of unreinforced masonry.